1998
DOI: 10.1161/01.str.29.10.2114
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Survival and Recurrence After Stroke in Malmö, Sweden

Abstract: Background and Purpose-Data from the Malmö Stroke Registry were analyzed to determine whether any change in survival or nonfatal stroke recurrence rates had occurred during the 4-year period from 1989 through 1992 and whether prognosis was related to area of residence. Methods-The series comprised 2290 patients, 1051 men and 1239 women, followed up for 3 years after their first stroke during the period 1989 through 1992. Results-Of the series as a whole, 959(43.4%) died and 137(6%) suffered a second nonfatal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
4
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 14 publications
6
59
4
3
Order By: Relevance
“…According to other epidemiological studies from the city, there is no reason to believe that biased retrieval or validation of end points confounded the results. 27 Frequent AEB assessed by means of 24-hour ECG monitoring was associated with stroke in this population-based cohort of older men. We conclude that a high frequency of AEB is associated with an increased incidence of stroke.…”
Section: Discussionmentioning
confidence: 82%
“…According to other epidemiological studies from the city, there is no reason to believe that biased retrieval or validation of end points confounded the results. 27 Frequent AEB assessed by means of 24-hour ECG monitoring was associated with stroke in this population-based cohort of older men. We conclude that a high frequency of AEB is associated with an increased incidence of stroke.…”
Section: Discussionmentioning
confidence: 82%
“…Studies of stroke-survival prognoses among white Americans 20 and Canadians 11 showed diabetes to be a significant predictor of mortality independent of heart diseases. Similarly, analysis of stroke registry data in Sweden 10 showed that the presence of diabetes was a significant predictor of both mortality and recurrence in stroke patients during the period 1989 -1992. However, whether subjects had continuous treatment for diabetes was not considered in these 3 studies.…”
Section: Discussionmentioning
confidence: 94%
“…There was wide variation in definition of stroke recurrence used, ranging from any focal neurological deficit lasting for Ͼ24 hours occurring after an initial stroke 3,5,14,19 to an exclusion period of 28 days, only after which further strokes were considered a recurrence. 25, 26 Coull and Rothwell previously demonstrated the effect of different definitions of stroke recurrence on estimates of risk of recurrence 90 days after first stroke in the Oxford Vascular Study and Oxford Community Stroke Project cohorts. 27 They found that the risk of recurrence in Oxford Vascular Study and Oxfordshire Community Stroke Project, respectively, ranged from 18.3% to 14.5% when including all stroke recurrences occurring 24 hours after initial stroke, and from 5.9% to 4.8% using the definition used in the Monitoring Trends and Determinants in Cardiovascular Disease study and other population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that strokes with an atherosclerotic origin recur earlier than other stroke subtypes; therefore, by excluding recurrent strokes occurring in the first weeks after initial stroke, artificially lower risk of stroke recurrence may be reported. 25 The studies included in this review have a combined study period encompassing 50 years (Table). Temporal trends in stroke management and, in particular, the advent and increasing importance given to secondary prevention after initial stroke may be another important contributory factor of variation in risk of recurrence during this period.…”
Section: Discussionmentioning
confidence: 99%